Study on the promotion effect of informationization on entrepreneurship: An empirical evidence from China - Longpeng Zhang; Wei Jiang; Zhiwei Tang (Journal of Global Entrepreneurship Research, 2019)
With the in-depth development of informatization, the role of new ventures and small and micro enterprises in economic growth has become increasingly prominent. However, rare literature systematically studies the impact of informatization on entrepreneurship. Based on the data from the 2011 China Household Finance Survey and the Report of China Informationization Development Assessment (2013), this paper uses the probit model, the multiple-choice probit model, and the Heckman two-stage model to examine the influence of informationization on entrepreneurial choices and entrepreneurial performance. The research finds the following conclusions. Firstly, informationization not only significantly improves the probability of entrepreneurship, but also facilitates the realization of income and employment effects from entrepreneurship. Secondly, information infrastructure, government informationization, and resident informationization, as informationization dimensions, can significantly increase the probability of entrepreneurship, although enterprise informationization plays an opposite role. Finally, the influence of informationization on promoting entrepreneurship varies with entrepreneurial type and entrepreneurial industry.
Keywords: 650; Informationization; Entrepreneurial choices; Entrepreneurial performance; Promotion effect